(untitled) (Revista de Estudos da Linguagem, 2024)
The aim of this text is to offer an overview of current research directions in comparative syntax and semantics, considering a brief history of the two areas and their current international trends. As Contrastive Linguistics still presents relatively incipient development in Portuguese-speaking areas, the main paths of research in diachronic syntax and semantics are presented in the formalist, functionalist and variationist strands, as well as the research groups that represent them, especially in Brazil and Portugal. Finally, the contributions of the articles that make up the special issue that accompanies this text are described, as well as a reflection on the directions that they point for future studies.